2022
DOI: 10.3390/s22124557
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Temperature Variations and Extreme Temperature Differences for the Corrugated Web Steel Beams under Solar Radiation

Abstract: Due to the coupling impacts of solar radiation, wind, air temperature and other environmental parameters, the temperature field of steel structures is significantly non-uniform during their construction and service stages. Corrugated web steel beams have gained popularity in structural engineering during the last few decades, while their thermal actions are barely investigated. In this paper, both experimental and numerical investigations were conducted to reveal the non-uniform features and time variation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…In this paper, the data were analyzed using the visual analysis method, i.e., the polar difference method. The "extreme difference" is a way to visualize the influence of the factors in the test, expressed numerically; the greater the value of the extreme difference, the greater the influence of the factor and vice versa [19][20][21].…”
Section: Nanopowder-cement-modified Silty Soil Orthogonal Testmentioning
confidence: 99%
“…In this paper, the data were analyzed using the visual analysis method, i.e., the polar difference method. The "extreme difference" is a way to visualize the influence of the factors in the test, expressed numerically; the greater the value of the extreme difference, the greater the influence of the factor and vice versa [19][20][21].…”
Section: Nanopowder-cement-modified Silty Soil Orthogonal Testmentioning
confidence: 99%
“…Abid et al [32] conducted an FE thermal analysis to investigate the behavior of the temperatures across the steel girder section and along the girder depth, finding that the thermal gradient variations at the top and bottom surfaces were comparable. Shiji Huang et al [33] used experimental and numerical thermal analysis methods to investigate the nonuniform and time-dependent temperatures of corrugated web steel beams under environmental thermal loads. To study the effect of the location and its corresponding climatic conditions, a thermal analysis study was conducted for eight cities.…”
Section: Experimental and Numerical Thermal Analyses Of Temperature D...mentioning
confidence: 99%
“…The results indicated a complex and nonuniform action of the steel girder. The maximum temperature difference of approximately 47 • C was determined in the steel girder [33]. Wucheng Xu et al [34] showed that the heat exchange between the different solar radiation components, heat convection and other factors and the boundaries of the steel structures resulted in a significant nonuniform distribution of the temperatures in steel structures.…”
Section: Experimental and Numerical Thermal Analyses Of Temperature D...mentioning
confidence: 99%
“…Li et al [24] proposed that large temperature changes and strong solar radiation would hinder concrete temperature control and crack prevention. Zhu et al [25] proposed that the seasonal variation in the solar azimuth angle will make the solar radiation absorbed by different regions of high arch dams vary greatly, which may lead to an uneven temperature distribution on the surface of high arch dams and then to adverse stress in the construction and operation of high arch dams. Chang et al [26] calculated the influence of solar radiation on the temperature state of a roller compacted concrete (RCC) dam in the high-temperature season and determined that the calculated temperature field considering the influence of sunshine was closer to the actual temperature field.…”
Section: Introductionmentioning
confidence: 99%